Management of generalized gingivitis associated with malnutrition: Management of generalized gingivitis associated with malnutrition - Syaikah, Aliya; Nadia, En; Permatasari, A S (Makassar Dental Journal, 2025)
Malnutrition is defined as insufficient, unbalanced, or excessive intake of macronutrients, micronutrients, or both. Malnutrition does not cause periodontal disease, but it increases the risk of its occurrence and accelerates its progression. This study observed changes in the periodontium of malnourished children after treatment. A boy came to the Unhas Dental Hospital after being re-ferred from a hospital, complaining of swollen gums, bright red colour, and easy bleeding, especially when eating and brushing his teeth. The patient tended to eat soft foods, was born with a history of low birth weight, had frequent fevers, and had no history of seizures or drug allergies. Upon examination, his weight was 17 kg, and he appeared pale. Intraorally, his OH was poor, with gi-ngival enlargement, bright red, and easy bleeding. Laboratory tests and consultation with a paediatrician revealed no blood dis-orders or systemic diseases, and he was prescribed multivitamins. After one session of DHE and manual supragingival scaling by the dentist, improvement in the gums was observed. The patient also began to be able to eat more solid foods. It was conclu-cluded that nutritional improvement and the elimination of plaque and calculus factors are effective in managing generalised gi-ngivitis influenced by malnutrition.